Philosophy and Meditation - Charles Herrman (University of Warsaw, 2021)
Preview: /Review: Michael Webb, The Whole at Once: A Conversation on Meaning (Austin,TX: Fire Hill Press, 2020), 244 pages./ This is a book about a phenomenological challenge: to reach the depths of meaning. It relies principally on becoming aware of the self and of the core essence of wholes, be they collections of objects or sentences or ideas. But meaning is the end point constituting, according to the author, a drive more powerful even than the will to live (WO, 137). It lies beyond any given perspective. The work is presented as a dialogue between student and master; its 244 pages actually make for a quick and relatively easy read, not burdening the reader with jargon. It intends to be a popular presentation but without skimping on issues of relevance to philosophy.